2016
DOI: 10.1200/jco.2016.67.7732
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Phase II Study of Lenalidomide in Relapsed or Recurrent Adult T-Cell Leukemia/Lymphoma: ATLL-002

Abstract: Purpose Few treatment options exist for adult T-cell leukemia/lymphoma (ATL), and the prognosis for this disease is poor. A phase I study of lenalidomide demonstrated preliminary antitumor activity in patients with relapsed ATL. The current phase II study evaluated the efficacy and safety of lenalidomide monotherapy in patients with relapsed or recurrent ATL. Patients and Methods Patients 20 years of age or older with acute, lymphoma, or unfavorable chronic subtype ATL, who had received one or more prior anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
131
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 119 publications
(139 citation statements)
references
References 44 publications
6
131
0
Order By: Relevance
“…Recently, for aggressive ATL, several promising therapeutic antibodies, such as anti‐CC chemokine receptor 4 mAb and an anti‐CD52 antibody, have been introduced and have achieved significant reduction of ATL cells. Furthermore, lenalidomide, an immune‐modulatory agent, has been introduced for relapsed aggressive ATL patients . In Europe and America, an antiviral therapy with a combination of zidovudine (AZT) and interferon‐α has been introduced for ATL patients with leukemic manifestation .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, for aggressive ATL, several promising therapeutic antibodies, such as anti‐CC chemokine receptor 4 mAb and an anti‐CD52 antibody, have been introduced and have achieved significant reduction of ATL cells. Furthermore, lenalidomide, an immune‐modulatory agent, has been introduced for relapsed aggressive ATL patients . In Europe and America, an antiviral therapy with a combination of zidovudine (AZT) and interferon‐α has been introduced for ATL patients with leukemic manifestation .…”
Section: Discussionmentioning
confidence: 99%
“…To enhance the GvATLL effect and to avoid the toxicity of GVHD, new molecular target therapies for ATLL are being investigated. Two promising new agents are mogamulizumab and lenalidomide . In particular, considering the increasing number of cord blood transplantations for patients with ATLL who cannot receive DLI, these agents might enhance GvATLL by immunomodulation after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the novel agents, the findings of a phase 2 study on lenalidomide showed a promising overall response rate and survival in relapsed and recurrent patients with aggressive ATL. 8 Furthermore, several clinical trials on novel agents such as the histone deacetylase inhibitors, alemtuzumab, brentuximab vedotin, nivolumab, and an EZH1/ 2 dual inhibitor are currently in progress. This novel prognostic model would be useful for risk-adapted therapeutic intervention in the future.…”
Section: Discussionmentioning
confidence: 99%
“…A phase 2 study of lenalidomide in relapsed or recurrent patients with aggressive ATL showed an overall response rate, median progression-free survival, and MST of 42%, 3.8 months, and 20.3 months, respectively. 8 In terms of antiviral therapies, the effect of a combination of IFN/AZT on patients with ATL was reported in 1995 for the first time. 9,10 Gill et al reported the overall response rate of 58% and MST of 3 months in 19 aggressive ATLs, including 12 patients previously treated.…”
Section: Indolent Atlmentioning
confidence: 99%